High-coverage paleo-genome research identifies a pathogenic mutation on EXT1 in a Qing-period Chinese individual with multiple osteochondromas - Bangyan Wang; Haodong Chen; Fanhao Xi; Haoquan Bao; Hetong Wen; Panxin Du; Chenshuang Sun; Jianxue Xiong; Baoshuai Zhang; Xin Chang; Yawei Zhou; Chuan-Chao Wang; et al. (Molecular Genetics and Genomics, 2026)

Light-triggered molecular lever in a MOF@COF nanosheet for synergistic enhancement of heat and mass transfer in CO2 photothermal desorption - Jingyu Bao; Mingjie Zhou; Zuxue Bai; Yawei Xie; Xuehui Jia; Jiajun Zeng; Yujie Huang; Ruimeng Wang; Jianmin Chen; Zhaowei Jia; Liqin Zhou; Zhongxing Zhao; et al. (Chemical Engineering Journal, 2026)

Enhanced net carbon dioxide sink in rice-duckweed system: Evidence from the diurnal flux variation - Weixuan Liu; Ning Gao; Yawei Li; Xiaoyin Liu; Xue Zhou; Yihao Peng; Lili Zhu; Jian Meng; Junzeng Xu (Agriculture, Ecosystems & Environment, 2026)

Rhizosphere reactive oxygen species as a protective barrier suppress Fusarium oxysporum invasion in tomato - Yaru Zhu; Huiqiang Yang; Siqi Shen; Meng Liu; Zelin Hao; Yawei Zhou; Jinbo Liu; Hanzhong Jia (Environmental Chemistry Letters, 2026)

A proton-relay strategy with K-modulated N/P proton pairs over Ru-based catalysts for efficient ammonia decomposition - Shuyu Chen; Rui Chen; Liang Wang; Haibo Tang; Rui Wang; Tian Tian; Yawei Zhou; Zihan Meng; Haolin Tang (Chemical Engineering Journal, 2026)

Prenatal Chromium Exposure and Gestational Diabetes Mellitus: Integrating Genetic and Epigenetic Regulation of LPCAT1 from a Phospholipid Remodeling Perspective - Yuxin Tian; Lu Yao; Jiaqi Zhang; Meng Zhou; Yue Dou; Bole Zhang; Yulin Li; Yongliang Feng; Yawei Zhang; Suping Wang; Weiwei Wu (Biological Trace Element Research, 2026)

CLEC14A mediates trophoblast dysfunction in unexplained miscarriage by disrupting the cAMP/ERK signaling pathway - Jianing Wang; Yawei Shao; Linlin Zhou; Ruyue Ma; Shunli Dong; Ruiheng Zhao (Journal of Molecular Histology, 2026)

Microplastic-pathogen interactions differentially modulate tomato Fusarium wilt severity: The dependence of polymer biodegradability - Siqi Shen; Yawei Zhou; Ru Zhao; Meng Liu; Wenjiang Fu; Shuting Zhao; Chaokai Yan; Qi Gao; Dan Zhang; Yanhua Wang; Hanzhong Jia; Yahong Wei (Journal of Hazardous Materials, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

An ensemble method for integrating rainfall forecast products based on average mutual information decomposition - Wei Ding; Minglei Ren; Yawei Ning; Xuan Li; Jinnan Zhang; Huicheng Zhou (Environmental Modelling & Software, 2026)

Hepatocellular carcinoma with microvascular invasion: from theory to clinical practice - Tong Yuan; Yawei Fan; Honghao Zhou; Chengjian Shi; Qi Cheng; Erlei Zhang (Science China Life Sciences, 2026)

Brine-filled MXene “Sandwich” system for synergistically enhanced electrochemical energy storage and solar desalination - Bowen Liu; Xuedong He; Yawei Yang; Yuyao Shen; Yihong Liu; Qi Zhao; Xinye Xu; Mo Zhou; Tianyi Wang; Wenxiu Que (Chemical Engineering Journal, 2026)

Elaborating PFAS characteristics for Chinese electroplating industry by target and nontarget analysis - Bo-Xuan Zhang; Xiang-Zhou Meng; Bao-Cang Han; Zhen Zhao; Qin-Wen He; Cun-Di Ma; Qinghe Zhu; Jie Yang; Haiyan Qin; Yawei Wang (Water Research, 2025)

Rational design of an ultra-high-gain MoS2 phototransistor enabling room-temperature detection of few-photon signals and attomolar-level immunosensing - Zhengdao Xie; Yun Hui; Wenhua Zhou; Shengxuan Xia; Yawei Lv; Liwei Ouyang; Yang Chai; Xingqiang Liu; Bei Jiang; Chang Liu; Sen Zhang; Chenchen Chu; et al. (Science Bulletin, 2025)

Investigation on the effect of nanocellulose-enhanced short-chain fluorocarbon foam parameters on gasoline pool fire extinguishing performance - Yawei Lu; Jiahao Lai; Shaolin Liang; Xingyan Cao; Zhirong Wang; Yangqing Zhou (Process Safety and Environmental Protection, 2025)

Effect of catalysts on the conversion of sulfur, nitrogen, and oxygen during catalytic/additives pyrolysis of oil sludge - Zhiguo Zheng; Zhipu Wang; Sikai Wu; Guangpu Li; Yawei Zhai; Lisong Zhou; Jun Yao (Journal of Environmental Chemical Engineering, 2025)

Mechanism and application of phenyllactic acid on the control of yogurt post-acidification caused by Lactobacillus bulgaricus - Hongxin Zhou; Xuanxuan Pang; Panpan Han; Zhixin Wang; Shijie Wang; Yingmin Jia; Yawei Ning (Food Research International, 2025)

Sufficient burial depth is a prerequisite for Chinese cyclina (Cyclina sinensis) to maintain normal life activities - Yurou Ma; Shiyu Yan; Zhengyu Shao; Guolong Zhou; Ang Hu; Yawei Bu; Huimin Wang; Xinqi Lv; Jianyu Liu; Yihua Chen; Zhiguo Dong (Aquaculture, 2025)

Soil pH modulates the impact of ammonia-based fertilizers on N-cycling microbial genes in terrestrial ecosystems - Xue Zhou; Yiyun Chen; Yawei Li (European Journal of Soil Biology, 2025)

Self-assembling biocompatible core-shell nanocapsules with versatile surface functionalities for precise pesticide delivery - Chunlin Yang; Zaiyu Lu; Chunhui Zhou; Xiang Yao; Yawei Tang; Xiuxia Li; Junjun Wang; Lihong Zhang (Chemical Engineering Journal, 2025)

Ancient genomes shed light on the long-term genetic stability in the Central Plain of China - Hao Ma; Yawei Zhou; Rui Wang; Fei Yan; Haodong Chen; Limin Qiu; Jing Zhao; Li Jin; Chuan-Chao Wang (Science Bulletin, 2025)

Titanium-based hollow fiber membrane: Fabrication, optimization, and electrochemical filtration treatment performance - Xiaoqing Yan; Zonglin Pan; Xinyuan Zhou; Shuo Liu; Hang Yu; Ruisong Xu; Yawei Shi; Xinfei Fan; Tianjun Sun; Yongxin Song; Chengwen Song (Journal of Environmental Chemical Engineering, 2025)

Lovastatin enhances humoral and cellular immune responses to H1N1 influenza vaccine - Zuchen Song; Yantong Zhou; Lina Jiao; Tianyu Zhu; Ruihong Yu; Zheng Wang; Yawei Qiu; Jinfeng Miao; Ting Cai; Shun Zhang; Huina Liu; Haifeng Sun; et al. (Veterinary Microbiology, 2025)

Duckweed (Lemna minor L.) as a natural-based solution completely offsets the increase in ammonia volatilization induced by soil drying and wetting cycles in irrigated paddies - Weixuan Liu; Junzeng Xu; Yawei Li; Xiaoyin Liu; Xue Zhou; Yihao Peng; Yixuan Jia; Jian Gao; Qianjing Jiang; Yong He (Science of The Total Environment, 2024)

Pressure retarded osmosis enhanced by micro-nano bubbles: Coupling effects of operation conditions and mass transfer resistance analyses - Yawei Du; Jiangbo Dai; Wuao Zhou; Lijin Ma; Jingxin Wei; Lixin Xie; Huining Deng; Shaofeng Zhang (Desalination, 2024)

Optimized multi-point hemispherical grid model with adaptive grid division based on the prior information of multipath error - Xuan Zou; Yawei Wang; Zhiwen Wu; Weiming Tang; Chen Zhou; Zhiyuan Li; Chenlong Deng; Yangyang Li; Yongfeng Zhang (Advances in Space Research, 2024)

Molecular designing of potential environmentally friendly PFAS based on deep learning and generative models - Ying Yang; Zeguo Yang; Xudi Pang; Huiming Cao; Yuzhen Sun; Ling Wang; Zhen Zhou; Pu Wang; Yong Liang; Yawei Wang (Science of The Total Environment, 2024)

Characteristics of disinfection byproducts from dissolved organic matter during chlor(am)ination of source water in Tibetan Plateau, China - Ruiqing Chen; Tianyu Chen; Yukun Zhou; Linfeng Li; Lingxiangyu Li; Nali Zhu; Zhigang Li; Yawei Wang; Guibin Jiang (Science of The Total Environment, 2024)

Prevalence of antibiotic resistance genes, heavy metal, and bacterial community composition in sea sediments influenced by Eriocheir sinensis breeding aquaculture - Hui Fu; Wei Sun; Yawei Cao; Qing Li; Xiaotong Wang; Zijie Zhou; Qian Meng; Tingyi Luo; Wei Gu; Qingguo Meng (Environmental Science and Pollution Research, 2024)

Effects of basic amino acids on heterocyclic amines and quality characteristics of fried beef patties at low NaCl level - Pinghua Deng; Shuang Teng; Yu Zhou; Yuling Liu; Boqun Liao; Xiaopu Ren; Yawei Zhang (Meat Science, 2024)

Hollow engineering of Co/N-doped C@carbon aerogel with hierarchical structure boosting interfacial polarization for ultra-thin microwave absorption and thermal insulation - Panpan Zhou; Shiyu Zhang; Wei Zhou; Chencheng Sun; Chengyao Hu; Shilin Yuan; Jiarui Li; Chang Liu; Yuchen Zhao; Yawei Kuang; Shuchang Wang; Qitu Zhang; et al. (Chemical Engineering Journal, 2024)

Low-permittivity BaCuSi4O10-based dielectric Ceramics: An available solution to connect low temperature cofired ceramic technology and millimeter-wave communications - Wei Wang; Xin Wang; Jian Bao; Jiapei Jiang; Zhen Fang; Biaobing Jin; Zhongqi Shi; Moustafa Adel Darwish; Yawei Chen; Qixin Liang; Meirong Zhang; Diming Xu; et al. (Chemical Engineering Journal, 2024)

Exogenous iron caused osteocyte apoptosis, increased RANKL production, and stimulated bone resorption through oxidative stress in a murine model - Zengfeng Guo; Jiawen Wu; Yawei Hu; Jianhua Zhou; Qingmei Li; Yandong Zhang; Junde Zhang; Linbo Yang; Shenghang Wang; Hao Zhang; Jiancheng Yang (Chemico-Biological Interactions, 2024)

SPAN secondary particles enabled high energy density Lithium-Sulfur battery - Weijing Zuo; Rui Li; Xiangkun Wu; Yawei Guo; Shoubin Zhou; Bohua Wen; Jiayan Luo; Lan Zhang (Chemical Engineering Journal, 2024)

Process optimization of high purity CO2 compression and purification system from oxygen-rich combustion flue gas - Lijin Ma; Yawei Du; Xiaojun Guo; Wuao Zhou; Huining Deng; Shaofeng Zhang (International Journal of Greenhouse Gas Control, 2024)

Experimental study on the progressive collapse mechanism of excavations retained by tied-back retaining systems - Gang Zheng; Ruozhan Wang; Xuesong Cheng; Qiang Zhou; Yawei Lei; Shixiong Wu; Fan Yi (Tunnelling and Underground Space Technology, 2024)

Photo-Enhanced Lead-Free Antimony-Based perovskite triboelectric nanogenerator for Dual-Mode detector - Ling Ding; Zhan Wei; Na Sun; Yawei Cai; Yanhong Zhou; Kan Fang; Guigen Wang (Chemical Engineering Journal, 2024)

Pollution levels and probability risk assessment of potential toxic elements in soil of Pb–Zn smelting areas - Mingyue Li; Jinyang Zhou; Zhiwen Cheng; Yuanyang Ren; Yawei Liu; Linling Wang; Liu Cao; Zhemin Shen (Environmental Geochemistry and Health, 2024)

Surviving punishment by body reduction in a hierarchical society: A bioarcheological study of two punitive amputation cases in Eastern Zhou Dynasty (771–256 BCE) with references to the penal and medical systems of ancient China - Yawei Zhou; Yanmei Liu; Fei Yan; Qian Wang (Archaeological and Anthropological Sciences, 2024)

Integrating Software FMEA and STPA to Develop a Bayesian Network-Based Software Risk Model for Autonomous Ships - Xue Yang; Yawei Zhu; Tao Zhou; Sheng Xu; Wenjun Zhang; Xiangyu Zhou; Xiangkun Meng (Journal of Marine Science and Engineering, 2023)
The autonomous shipping industry is increasingly focusing on enhancing the safety and reliability of software-based systems. Conducting a risk assessment is a requirement for demonstrating the safety equivalence of autonomous ships based on such systems to conventional vessels. Traditional risk assessment models, however, primarily focus on hardware failures, often overlooking potential software-related failures and functional inadequacies. This study proposes a framework integrating Software Failure Mode and Effects Analysis (FMEA), System–Theoretic Process Analysis (STPA), and Bayesian Network (BN) for risk identification of autonomous ship software systems. The results of a case study reveal that the framework sufficiently addresses the multifaceted nature of risks related to software in autonomous ships. Based on the findings of this study, we suggest the need for standardization of software architecture development in the autonomous ship industry and highlight the necessity for an enhanced understanding of AI-specific risks and the development of tailored risk assessment methodologies.

Experimental research on the venting characteristics of methane and coal dust two-phase system mixture explosions - Xingyan Cao; Rui Huang; Yawei Lu; Zhirong Wang; Longtao Fan; Yangqing Zhou; Jianjun Xu (Fuel, 2023)

Development of near-infrared reflectance spectroscopy (NIRS) model and genome-wide association study for glycogen and protein content in Pacific abalone - Junyu Liu; Muzhi Zhou; Ziheng Yin; Dan Huang; Liyan Zhu; Weiguang Zou; Wenchao Yu; Yawei Shen; Zekun Huang; Weiwei You; Caihuan Ke; Xuan Luo (Aquaculture, 2023)

Experimental investigation on a novel and hyper-efficient oscillating water column wave energy converter coupled with a parabolic breakwater - Robert Mayon; Dezhi Ning; Yawei Sun; Zhenyu Ding; Rongquan Wang; Yu Zhou (Coastal Engineering, 2023)

SIRT1 regulates osteoblast senescence through SOD2 acetylation and mitochondrial dysfunction in the progression of Osteoporosis caused by Cadmium exposure - Dehui Zhou; Yawei Ran; Rui Yu; Gang Liu; Di Ran; Zongping Liu (Chemico-Biological Interactions, 2023)

Examining the impacts of implicit economic policy on urban environmental pollution: Unveiling pathways for sustainable recovery - Ya Yang; Mengru Zhou; Yawei Hou; Run Tang; Bo Liu; Yue Deng (Resources Policy, 2023)

Nrf2 protects against renal fibrosis induced by chronic cadmium exposure in mice - Chengjie Chen; Zhengsheng Zhou; Siqi Yu; Yawei Ma; Gang Wang; Xue Han; Congcong Jiao; Junjun Luan; Zhiyuan Liu; Yuanyuan Xu; Huihui Wang; Qiang Zhang; et al. (Food and Chemical Toxicology, 2023)

Community Characteristics of Soil Ectomycorrhizal Fungi under Different Forests in the Sandy Areas of Northeastern China - Jiaying Liu; Changjun Ding; Weixi Zhang; Yawei Wei; Yongbin Zhou; Wenxu Zhu (Journal of Soil Science and Plant Nutrition, 2023)

Flood Risk Quantification, Transmission, and Propagation Analysis for Flood Water Utilization of Parallel Reservoirs - Wei Ding; Chi Zhang; Jie Lin; Xi Zhao; Yawei Ning; Huicheng Zhou (Journal of Hydrology, 2023)

From bitter to delicious: properties and uses of microbial aminopeptidases - Yawei Wang; Puying Zhao; Ying Zhou; Xiaomin Hu; Hairong Xiong (World Journal of Microbiology and Biotechnology, 2023)

Innovative calcium-doped layered yttrium hydroxides for rapid and efficient removal of fluoride from aqueous solutions: Insight into adsorption mechanism - Ying Liang; Fengjie Chen; Meng Zhang; Lufeng Chen; Yu Xia; Zhen Zhou; Bolei Chen; Lixia Zhao; Yong Liang; Yawei Wang (Journal of Environmental Chemical Engineering, 2023)

Development of a synthetic transcription factor-based S-adenosylmethionine biosensor in Saccharomyces cerevisiae - Yawei Chen; Huijie Zheng; jiajia Yang; Yiting Cao; Huiyun Zhou (Biotechnology Letters, 2023)

Effects of Different Levels of Organic Trace Minerals on Oxidative Status and Intestinal Function in Weanling Piglets - Shangchu Wang; Shujun Wu; Yawei Zhang; Juan Chen; Xihong Zhou (Biological Trace Element Research, 2023)

Bond behavior of an ultra-high performance concrete-filled anchorage for carbon fiber-reinforced polymer tendons under static and impact loads - Yawei Fang; Zhi Fang; Lixin Feng; Yu Xiang; Xuhong Zhou (Engineering Structures, 2023)

Radial and seasonal variation of sap flow and its response to meteorological factors in sandy Pinus sylvestris var. mongolica plantations in the Three North Shelterbelt of China - Yuqiang Tong; Jing Liu; Xu Han; Tong Zhang; Yinghao Dong; Mengge Wu; Shengjin Qin; Yawei Wei; Zhenju Chen; Yongbin Zhou (Agricultural and Forest Meteorology, 2023)

Sestrin2 attenuates renal damage by regulating Hippo pathway in diabetic nephropathy - Yawei Bian; Chonglin Shi; Shan Song; Lin Mu; Ming Wu; Duojun Qiu; Jiajia Dong; Wei Zhang; Chen Yuan; Dongyun Wang; Zihui Zhou; Xuan Dong; et al. (Cell and Tissue Research, 2022)

Twin peaks of in-hospital mortality among patients with STEMI across five phases of COVID-19 outbreak in China: a nation-wide study - Jianping Li; Nan Zhang; Ziyi Zhou; Xiao Huang; Weiyi Fang; Hongbing Yan; Jiyan Chen; Weimin Wang; Dingcheng Xiang; Xi Su; Bo Yu; Yan Wang; et al. (Science China Life Sciences, 2022)

Numerical Investigation on Higher-Order Harmonic Waves Induced by a Submerged Inclined Plate - Zhimin Zhou; Yawei Sun; Lifen Chen; Dezhi Ning; Sulisz Wojciech (Journal of Marine Science and Engineering, 2022)
In this paper, a two-dimensional time-domain numerical flume has been established to model and investigate nonlinear interactions between nonlinear surface waves and a submerged inclined thin plate. The model solves the Laplace equation and the fully nonlinear free surface boundary conditions within the framework of potential flow theory based on the high-order boundary element method. The mixed Euler–Lagrangian method is applied to update the water surface at each time step, and the fourth-order Runge–Kutta method for time stepping. A so-called four-point method was employed to separate the second-order harmonic free and bounded wave that has the same wave frequency but different wave celerity in front of and behind the submerged plate. It is found that the amplitude of the second-order harmonic free wave increases with the inclination angle of the submerged plate, and the level/amount of the increase is larger for a larger wave steepness. In addition, the amplitudes of both the second-order reflected and transmitted waves are found to increase with the wave steepness, and their empirical relationships are derived for potential use in practical engineering.

Design and evaluation of chitosan-amino acid thermosensitive hydrogel - Jianan Tong; Huiyun Zhou; Jingjing Zhou; Yawei Chen; Jing Shi; Jieke Zhang; Xinyu Liang; Tianyuan Du (Marine Life Science & Technology, 2022)

The neonatal PROC gene rs1799809 polymorphism modifies the association between prenatal air pollutants exposure and PROC promoter methylation - Zhiyuan Li; Meng Yang; Leizhen Duan; Yongxiang Gong; Hongxia Xia; Francis-Kojo Afrim; Hui Huang; Xiaoxue Liu; Fangfang Yu; Yawei Zhang; Yue Ba; Guoyu Zhou (Environmental Science and Pollution Research, 2022)

Characterization of plant growth-promoting traits of Enterobacter sp. and its ability to promote cadmium/lead accumulation in Centella asiatica L. - Yi Li; Lijuan Mo; Xiaoqin Zhou; Yawei Yao; Jiangming Ma; Kehui Liu; Fangming Yu (Environmental Science and Pollution Research, 2022)

Promoter methylation and expression of the rassf4 gene in Nile tilapia ( Oreochromis niloticus ) - Yawei Shen; Huiyang Li; Min Zhou; Shoujie Tang; Yan Zhao; Jinliang Zhao; Xiaowu Chen (Journal of Fish Biology, 2021)
Oreochromis niloticus RAS‐association domain family 4 ( rassf4 ) was specifically expressed in the ovaries. Immunohistochemistry results showed that Rassf4 was located in follicular cells. The methylation percentages of the promoter region (−734/−1012) of rassf4 in the ovaries and testes were 13.28% and 92.85%, respectively. Deleting the fragment of −734 to −1012 sites significantly reduced the basal activity of the rassf4 promoter to 62.33%, which indicated that this region was important for the transcription of the rassf4 gene. This study lays the foundation for further research on the function of fish rassf4 .

An Analytical Risk Analysis Method for Reservoir Flood Control Operation Considering Forecast Information - Yawei Ning; Wei Ding; Guohua Liang; Bin He; Huicheng Zhou (Water Resources Management, 2021)

Tocilizumab for treating COVID-19: a systemic review and meta-analysis of retrospective studies - Meng Zhao; Jieyu Lu; Yihu Tang; Yawei Dai; Jingxin Zhou; Yanhu Wu (European Journal of Clinical Pharmacology, 2021)

Preconception ambient temperature and preterm birth: a time-series study in rural Henan, China - Guoyu Zhou; Meng Yang; Jian Chai; Renjie Sun; Junxi Zhang; Hui Huang; Yawei Zhang; Qihong Deng; Lifang Jiang; Yue Ba (Environmental Science and Pollution Research, 2021)

Winner takes all: reconstructing the decapitation of a warrior in Bronze Age China from osteological evidence - Yawei Zhou; Shuang Lin; Rangping Qin; Hui-Yuan Yeh; Qun Zhang (Archaeological and Anthropological Sciences, 2020)
Decapitation is an ancient practice in Asia with inadequate research. The present study reports on the osteological examination of a headless skeleton excavated from a high-status tomb in Chu State style dating back to the late Warring States Period (ca. 3th century BC) in Lu’an, Anhui, China. The individual is identified as a victim of decapitation with five peri-mortem sharp force cut marks on the posterior parts of the cervical vertebrae, and another one on the right second metacarpal. Microscopic observation of the kerfs, the historical records and archaeological evidence support the speculation that the individual could be a warrior of Chu State, who is decapitated after being wounded during the war against the Qin State. The hacking implement and the sequences of the cut marks are further discussed to reconstruct the process of execution. This multidisciplinary reconstruction is the first scientific osteological analysis of the decapitation on the human remains from the Chinese Bronze Age. Moreover, it will enrich our knowledge of the decapitation phenomenon in terms of war and execution in ancient China.

Early evidence of trepanation along the Yellow River Basin in Neolithic China - Yawei Zhou; Shuang Lin; Wanfa Gu; Letian He; Qun Zhang; Hui-Yuan Yeh (Archaeological and Anthropological Sciences, 2020)
Trepanation is a long-lasting ancient practice found around the world with diverse motivations. However, the distribution and motivation of intentional trepanation in China remain unclear. This study presents one of the earliest trepanations on a male adult individual who is unearthed from the Shuanghuaishu site in Gongyi, Henan, dating back to the late Yangshao cultural period (3500–2900 BC). The macroscopic and microscopic observation, alongside with micro-CT scan, are conducted to further evaluate the conditions on the edges of the perforation and intracranial situation. The oval perforation is located on the occipital bone, and neither fracture nor apparent healing signs are observed on the margins. Archeological evidences and simulated experiment indicate that the trepanation could be conducted by drilling the tables of the skull with a V-bladed stone tool. In view of the location of the perforation and the limited details on the edges, the motivation behind the trepanation could be due to the medical treatment of trauma on the occipital bone or a postmortem ritual. The analysis of the early trepanation along the Yellow River Basin provides further evidence on the ancient human behavior and enriches our understanding of the origin and distribution of trepanation in Neolithic China.

Lithology identification and reservoir characteristics of the mixed siliciclastic-carbonate rocks of the lower third member of the Shahejie formation in the south of the Laizhouwan Sag, Bohai Bay Basin, China - Yajun Duan; Jun Xie; Baichuan Li; Mengqi Wang; Tianqi Zhang; Yawei Zhou (Carbonates and Evaporites, 2020)

Population susceptibility differences and effects of air pollution on cardiovascular mortality: epidemiological evidence from a time-series study - Mengyao Liu; Xiaoxia Xue; Baosen Zhou; Yawei Zhang; Baijun Sun; Jianping Chen; Xuelian Li (Environmental Science and Pollution Research, 2019)

A parameter-free progressive TIN densification filtering algorithm for lidar point clouds - Xiaotian Shi; Hongchao Ma; Yawei Chen; Liang Zhang; Weiwei Zhou (International Journal of Remote Sensing, 2018)

A novel 76-mer peptide mimic with the synergism of superoxide dismutase and glutathione peroxidase - Yawei Xu; Yan Zhou; Rui Yin; Cheng Wang; Haijiao Chu; Junling Wang (In Vitro Cellular & Developmental Biology - Animal, 2018)

Hyperthermostable Thermotoga maritima xylanase XYN10B shows high activity at high temperatures in the presence of biomass-dissolving hydrophilic ionic liquids - Tianyi Yu; Sasikala Anbarasan; Yawei Wang; Kübra Telli; Aşkın Sevinç Aslan; Zhengding Su; Yin Zhou; Li Zhang; Piia Iivonen; Sami Havukainen; Tero Mentunen; Michael Hummel; et al. (Extremophiles, 2016)

Biomass carbon storage and its sequestration potential of afforestation under natural forest protection program in China - Wangming Zhou; Bernard Joseph Lewis; Shengnan Wu; Dapao Yu; Li Zhou; Yawei Wei; Limin Dai (Chinese Geographical Science, 2014)

Forest carbon storage and tree carbon pool dynamics under natural forest protection program in northeastern China - Yawei Wei; Dapao Yu; Bernard Joseph Lewis; Li Zhou; Wangming Zhou; Xiangmin Fang; Wei Zhao; Shengnan Wu; Limin Dai (Chinese Geographical Science, 2014)

Land use effects on soil organic carbon, microbial biomass and microbial activity in Changbai Mountains of Northeast China - Xiangmin Fang; Qingli Wang; Wangming Zhou; Wei Zhao; Yawei Wei; Lijun Niu; Limin Dai (Chinese Geographical Science, 2014)